Efektivitas Hidroponik Tanaman Bunga Kana, Kayu Apu serta Ampas Kopi dalam Pengolahan Air Limbah Greywater Domestik - Nurhidayanti, Nisa; Ardiatma, Dodit (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2020)
Pelita Bangsa University is a developing private university in Bekasi Regency with an increasing number of students every year. The problem with the increasing number of students causes the domestic waste water produced to also increase. The purpose of this study was to determine the hydroponic effectiveness of Kana Flower and Apu wood and coffee grounds in reducing BOD, TSS, Oil and Fat of domestic greywater waste. The stages of the research method began with making activated charcoal from coffee grounds, taking wastewater samples, testing wastewater, acclimatizing plants, range finding tests, testing phytoreactors with activated carbon filters, and continuing with data analysis. The results of testing the parameters of domestic greywater waste with an activated carbon filter from coffee grounds for seven days obtained a final value of TSS <2.5 mg/l, BOD 23 mg/l, Oil and Fat of <0.1 mg/l, pH 7.61 and TDS of 286 ppm. The test results have met the quality standards for domestic wastewater according to the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number 68 of 2016. Based on the results of the study, it was found that the effectiveness of reducing the concentration of several parameters from the phytoremediation process with activated carbon filters from coffee grounds was a decrease in TSS of 98.20%, BOD 76.04%, oil and fat 0%, pH 0.39% and TDS 29.03%.